THE QUALITY OF LIFE OF YOUNG OFFENDERS IN JUVENILE JUSTICE INSTITUTIONS - Hassan, Nazirah (International Journal of Psychosocial Rehabilitation, 2020)
The increasingly number of contemporary youth crime and the escalating number of young people involved with the juvenile justice system have challenged established beliefs guiding policy and practice with young offenders. This paper investigates the quality of life among young offenders living in the juvenile justice institutions and how this influence their well-being and development. The study comprised a survey completed by 289 male and female young offenders, aged 12 to 21 years old, in 8 juvenile justice institutions in Malaysia, using the Measuring Quality of Prison Life (MQPL). Based on the analyses, majority of young people perceived moderate levels of quality of life in the institutions. Furthermore, sevensignificant dimensions of quality of life in the institutions have positive influence on the well-being and development of young people, including respect, staff- inmate relationship, humanity, bureaucratic legitimacy, fairness, safety and family contact. It is concluded thatpositive social climates in the institutions is an essential aspect of improving the effectiveness of institutions in rehabilitating young people. In contrast, poor quality of life in the institutions may lead young people to psychological distress, and thus increase their risk of reoffending.The paper concludes by recognizing the importance of policy improvement in the juvenile justice system.